HANDLING OF BULLYING BY THE SRAGEN SOCIAL SERVICE A COMPARATIVE STUDY OF ISLAMIC LAW AND NATIONAL LAW - Iqbal Abi Nusa; Abdul Fattaah (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
Bullying is a form of psychological and/or physical violence that frequently occurs in social environments, particularly among children and adolescents. Sragen Regency, as one of the regions in Central Java Province, also faces this issue and requires serious handling from various parties, including the Social Affairs Office. This study aims to analyze the efforts of the Sragen Regency Social Affairs Office in handling bullying cases and to compare the implementation of national law with the principles of Islamic law in addressing this problem. This research employs a qualitative approach with data collection techniques consisting of interviews, observation, and documentation. The results indicate that the Social Affairs Office has implemented various preventive and curative measures, such as socialization programs, psychological assistance, and cross-sectoral cooperation. From the perspective of national law, the handling of bullying is based on statutory regulations, particularly the Child Protection Act and the Criminal Code. Meanwhile, from the perspective of Islamic law based on the theory of maqasid al-shari’ah, bullying is categorized as an unjust act that violates the principles of justice and Islamic brotherhood (ukhuwah isl?miyah). The comparative study shows a convergence between national law and Islamic law in terms of victim protection, violence prevention, and law enforcement. However, Islamic law offers a more comprehensive moral and spiritual approach to resolution. This study recommends that the implementation of national law be more responsive by integrating Islamic legal values within the religious socio-cultural context of Sragen Regency.